Variation in the species richness of parasitoid wasps (Ichneumonidae: Pimplinae and Rhyssinae) across sites on different continents. Issue 3 (21st December 2017) - Gómez, Isrrael C.; Sääksjärvi, Ilari E.; Mayhew, Peter J.; Pollet, Marc; Rey del Castillo, Carmen; Nieves‐Aldrey, Jose‐Luis; Broad, Gavin R.; Roininen, Heikki; Tuomisto, Hanna
Abstract: The old idea that parasitoid wasps (Ichneumonidae) show an inverse latitudinal diversity gradient has recently been challenged, but how ichneumonid species richness varies across the globe is still not well understood. We carried out field inventories in 21 sites on three continents to clarify this question, focusing on the subfamilies Pimplinae and Rhyssinae. Our total sampling effort was 628 Malaise trap months and the total catch exceeded 65 000 individuals. Our main focus was in two intensively inventoried areas in Amazonia, together yielding 257 Malaise trap months and 26 390 ichneumonid individuals. To expand the scope and assess global species diversity patterns of the Pimplinae and Rhyssinae, we compiled published species lists from a total of 97 study localities around the world. The highest observed species richness in any locality, 105 species, was found in one of our field sites in Peruvian Amazonia. None of the other localities reported more than 70 species, even the ones with a sampling effort comparable to ours. Despite the local thoroughness of our field inventories in Amazonia, data analyses indicated that a substantial proportion of the parasitoid wasp species occurring in each site remained unobserved. The highest local species richness values were reported from the tropics. Nevertheless parasitoid wasps are still too sparsely sampled to draw solid conclusions about whether or not their species richness follows a particular latitudinal trend, and if so, where their richness peaks.